Case Report on Ulcerative Colitis in 16 year girl (World Journal of Current Medical and Pharmaceutical Research, 2020)
Ulcerative colitis (UC) is a chronic idiopathic inflammatory disorder that involves any part of the colon starting in the rectum in a continuous fashion presenting typically with symptoms such as bloody diarrhea, abdominal pain, and rectal urgency.The clinical presentation of the disease usually dictates the choice of pharmacologic therapy, where the goal is to first induce remission and then maintain a corticosteroid-free remission. UC is diagnosed based on clinical presentation and endoscopic evidence of inflammation in the colon starting in the rectum and extending proximally in the colon. The choice of treatment depends on severity, localization and the course of the disease. For proctitis, topical therapy with 5-aminosalicylic acid (5-ASA) compounds is used. More extensive or severe disease should be treated with oral and local 5-ASA compounds and corticosteroids to induce remission. Patients who do not respond to this treatment require hospitalization. Intravenous steroids or, when refractory, calcineurin inhibitors (cyclosporine, tacrolimus), tumor necrosis factor-α antibodies (infliximab) or immunomodulators (azathioprine, 6-mercaptopurine) are then called for. Indications for emergency surgery include refractory toxic megacolon, perforation, and continuous severe colorectal bleeding.